2017
DOI: 10.31219/osf.io/7e69g
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Continuation to upper secondary education in Finland: Children of immigrants and the majority compared

Abstract: The education of children of immigrants is an important aspect of the integration of immigrant groups into receiving societies. This article focuses on the first transition in the Finnish education system. Two aspects of the transition are analysed: continuation versus dropping out and choice of upper secondary school type (general versus vocational).Results suggest that children of immigrants tend to have a higher probability of dropping out of education at this transition than the majority. However, this can… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Previous research showed that migrants are more likely to choose academic tracks over vocational alternatives at upper-secondary level given that socio-economic status (SES) and school performance are held constant (Brinbaum and Cebolla-Boado, 2007; Jackson et al, 2012; Jonsson and Rudolphi, 2011; Kilpi-Jakonen, 2011; Van de Werfhorst and Van Tubergen, 2007). Recent European and US studies described ethnic choice effects as a general pattern (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research showed that migrants are more likely to choose academic tracks over vocational alternatives at upper-secondary level given that socio-economic status (SES) and school performance are held constant (Brinbaum and Cebolla-Boado, 2007; Jackson et al, 2012; Jonsson and Rudolphi, 2011; Kilpi-Jakonen, 2011; Van de Werfhorst and Van Tubergen, 2007). Recent European and US studies described ethnic choice effects as a general pattern (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, the existing evidence of ethnic choice effects in upper-secondary education is mainly based on studies in comprehensive educational systems such as Sweden, the UK, the US and Finland. In these contexts, ethnic choice effects were labelled as an ‘immigrant advantage’ and interpreted as a largely positive phenomenon (Jackson, 2012; Jonsson and Rudolphi, 2011; Kilpi-Jakonen, 2011). There remains, however, a lack of evidence on ethnic choice effects in education systems with strong vocational education and training (VET) sectors offering viable alternatives, such as Germany and Switzerland, with the latter being the focus of our study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, children of immigrants tend to exhibit high levels of educational aspirations. When other factors are controlled for, children of immigrants are found to be more likely to make educational transitions (Jackson, 2012 ; Jackson, Jonsson, & Rudolphi, 2012 ), more likely to favor general over vocational educations (Kilpi-Jakonen, 2011 ), and more likely to enter tertiary education (Kristen, Reimer, & Kogan, 2008 ). This phenomenon has been attributed to “immigrant optimism” (Feliciano & Lanuza, 2016 ; Fernández-Reino, 2016 ; Kao & Tienda, 1995 ), even though it is not exclusive to immigrant minorities.…”
mentioning
confidence: 99%
“…Finally, studies that considered the differential associations between risk factors and dropout as a function of immigration are scarce. We found only one study examining the differential association between students’ prior achievement, family resources, and dropout among first‐, second‐, and third‐generation students (Kilpi‐Jakonen, ). Results showed that second‐generation low‐achieving students who had a father outside the labour force were more likely to drop out compared to their native peers in a similar situation.…”
Section: Introductionmentioning
confidence: 99%